(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Studies were carried out on the leaves of Cassia alata. A flavone 3,5,7,4´-tetrahydroxy flavone was isolated as a new source from the leaves of Cassia alata with the help of column and thin layer chromatography using a gradient of organic solvents with increasing polarity. The compound was characterized on the basis of UV, IR, 1HNMR, 13C-NMR and Mass spectrometry. Bangladesh J. Sci. Ind. Res. 41(1-2), 93-96, 2006